1999
DOI: 10.1046/j.1365-2559.1999.035005423.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural localization of E‐cadherin and α‐/β‐catenin in adenoid cystic carcinoma

Abstract: These findings suggest that the neoplastic cells of ACC express E-cad for use in intercellular adhesion, but the cadherin-catenin complex might not operate properly, which is the cause of neoplastic cell dissociation, followed by invasion and metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0
8

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 43 publications
2
15
0
8
Order By: Relevance
“…Although basal cell adenocarcinoma is similar to basal cell adenoma, it has infiltrative growth, cellular atypia or mitotic figures; however, differential diagnosis is often difficult. E-cadherin is part of the cell adhesion complex where it is associated with b-catenin, and loss of E-cadherin and b-catenin has been associated with invasion or metastasis in a wide variety of human malignancies (5)(6)(7). On the other hand, nuclear localization of b-catenin is also known in a wide variety of tumors, such as familial adenomatous polyposis, colorectal cancer, adrenocortical adenoma, hepatocellular adenoma, craniopharyngioma, and solid-pseudopapillary neoplasm or intraductal papillary mucinous neoplasm of the pancreas (8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Although basal cell adenocarcinoma is similar to basal cell adenoma, it has infiltrative growth, cellular atypia or mitotic figures; however, differential diagnosis is often difficult. E-cadherin is part of the cell adhesion complex where it is associated with b-catenin, and loss of E-cadherin and b-catenin has been associated with invasion or metastasis in a wide variety of human malignancies (5)(6)(7). On the other hand, nuclear localization of b-catenin is also known in a wide variety of tumors, such as familial adenomatous polyposis, colorectal cancer, adrenocortical adenoma, hepatocellular adenoma, craniopharyngioma, and solid-pseudopapillary neoplasm or intraductal papillary mucinous neoplasm of the pancreas (8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…16,17 In the latter, a clear association was observed between mutation in b-catenin gene (CTNNB1) with tumorigenesis and tumor morphologic features. 18,19 Pleomorphic adenomas (PA) are the most common benign tumors of salivary glands. They occur more frequently in parotid, in young adults, slightly tending to females.…”
mentioning
confidence: 99%
“…R-cadherin could not be found on the plasmalemma where axons or Schwann cells were in contact with the basal lamina. Our previous study demonstrated that there was no difference between the results by the HRP method and by the immunogold method (Shibuya et al 1996). Consequently, it was clear that the distribution of R-cadherin was the same as that of N-cadherin under electron microscopy.…”
Section: Discussionmentioning
confidence: 89%